Relations between liver cadmium, cumulative exposure, and renal function in cadmium alloy workers. - Mason, H; Davison, A; Wright, A; Guthrie, C; Fayers, P; Venables, K; Smith, N; Chettle, DR; Franklin, D; Scott, M (1988)
Detailed biochemical investigations of renal function were made on 75 male workers exposed to cadmium and an equal number of referents matched for age, sex, and employment status. The exposed group consisted of current and retired workers who had been employed in the manufacture of copper-cadmium alloy at a single factory in the United Kingdom for periods of up to 39 years and for whom cumulative cadmium exposure indices could be calculated. In vivo measurements of liver and kidney cadmium burden were made on exposed and referent workers using a transportable neutron activation analysis facility. Significant increases in the urinary excretion of albumin, retinol binding protein, beta 2 microglobulin, N-acetylglucosaminidase (NAG), alkaline phosphatase, gamma-glutamyl transferase and significant decreases in the renal reabsorption of calcium, urate, and phosphate were found in the exposed group compared with the referent group. Measures of glomerular filtration rate (GFR) (creatinine clearance, serum creatinine, and beta 2 microglobulin) indicated a reduction in GFR in the exposed population. Many of these tubular and glomerular function indicators were significantly correlated with both cumulative exposure index and liver cadmium burden. Using cumulative exposure index and liver cadmium as estimates of dose, a two phase linear regression model was applied to identify an inflection point signifying a threshold level above which changes in renal function occur. Many biochemical variables fitted this model; urinary total protein, retinol binding protein, albumin, and beta 2 microglobulin gave similar inflection points at cumulative exposure levels of about 1100 y.micrograms/m3 whereas changes in the tubular reabsorption of urate and phosphate occurred at higher cumulative exposure indices. Measures of GFR, although fitting the threshold model did not give well defined inflection points. Fewer variables fitted the two phase model using liver cadmium; those that did gave threshold levels in the range 20.3-55.1 ppm. When cadmium workers with cumulative exposure indices of less than 1100 y.micrograms/m3 were compared with their respective referents only serum beta 2 microglobulin and urinary NAG were significantly increased in the exposed group and these differences were not related to the degree of cadmium exposure.(ABSTRACT TRUNCATED AT 400 WORDS)